The past and present scenario of avian influenza and its control strategy in Bangladesh: A review - Giasuddin, M; Ali, MZ; Karim, MR; Hassan, MZ; Hasan, M; Islam, E (Bangladesh Journal of Livestock Research, 2020)
Avian influenza virus (AIV) is a pandemic thread and this year 2018 is passing the century of Spanish flu (H1N1) of 1918 when the world approximately 50 million human deaths occurred worldwide. About 1.7 million peoples become died in over Asia from 1957 to till now by the name of Asian flu (H2N2) at 1957 and Hong Kong flu (H3N2) at 1968. In Bangladesh, since first identification of Highly Pathogenic Avian Influenza (HPAI) at 2007 poultry industry faces outbreaks at a significant level in every year although human infection is uncommon. The infections spreading among all major avian species like chicken, duck, turkey, quail. On the other hand it is reported that the infection is spreading among wild birds like house crow, migratory birds and wild animals also. During first isolation the virus were in clade 2.2.2 but after several mutations over 11 years now it becomes under clade 2.3.2.1a and circulating in environment. Government of Bangladesh decided to vaccinate against AIV in 2012 with two killed and one vector vaccine to combat the AIV that brings a satisfactory result. But from the couples of years again the incidence of AIV becomes very high and ongoing researches like sink surveillance shows 50-90% live bird markets of Dhaka and Chattagram districts are infected. To combat the AIV it is recommended that farms should have to ensure the good quality vaccine with good farm biosecurity practice along with conventional stamping out program. Bangladesh J. of Livestock Res. 21-25: 24-28, 2018